(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
We live in a digital environment where everything we do leaves a digital trace. Data are collected from various sources – social network posts, e-mails, sensors, image and video content, search engines, online sales, etc. The biggest reason for this growth of data could be found in technological advancement, since data can be easily and cheaply stored and shared today. This new trend in acquiring data demands a completely new approach to their processing and analysis. The aim of this paper, based on analysis of actual and relevant sources, is to present the situation and trends in the collection, processing, analysis and use of data that are complex, fast-growing, and diverse in type and content. In the introduction, the research problem has been defined. Afterwards, the term “Big Data” and its basic four dimensions have been explained. In the main part of the paper, the examples of Big Data analyses have been shown, as well as interesting results yielded by those analyses. Also, the special review about Big Data in management has been presented. Keywords: Big Data, data, management